2022
DOI: 10.46234/ccdcw2022.074
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19 Vaccination and Clinical Severity of Patients Infected with Delta or Omicron Variants — China, May 21, 2021–February 28, 2022

Abstract: What is already known about this topic?Compared with the international mRNA and adenovirus-vectored coronavirus disease 2019 (COVID-19) vaccines, there is less real-world research data about breakthrough cases in people vaccinated with China-made COVID-19 vaccines. Analyses of clinical outcomes of breakthrough cases will be an important supplement to the clinical trial efficacy and observational effectiveness data of China-made COVID-19 vaccines. What is added by this report? COVID-19 vaccine age-eligible indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 4 publications
5
34
0
Order By: Relevance
“…Recently, Zheng et al reported that full vaccination and a booster vaccination could protect old patients from pneumonia and serious COVID-19. 13 The kinds of vaccine, the doses of injection, and the duration between vaccination to infection may affect the protections provided by the vaccine. 10 , 17 Jassat et al reported that 37% of Omicron variant-infected patients had pneumonia in South Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zheng et al reported that full vaccination and a booster vaccination could protect old patients from pneumonia and serious COVID-19. 13 The kinds of vaccine, the doses of injection, and the duration between vaccination to infection may affect the protections provided by the vaccine. 10 , 17 Jassat et al reported that 37% of Omicron variant-infected patients had pneumonia in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Full vaccination and a booster vaccination can significantly protect old patients from pneumonia and serious COVID-19. 13 Considering that pneumonia is the most common manifestation of serious COVID-19, 14 analyzing the risk factors for pneumonia development in breakthrough cases with a history of inactivated vaccine injection is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 patients infected by the omicron variant of SARS-CoV-2 were hospitalized and treated as reported ( 17 ). Blood cell analysis was conducted by an automated XN1000 hematology analyzer (SYSMEX, Japan), and biochemical indicators were analyzed using VITROS 350 autoanalyzer (Johnson &.…”
Section: Methodsmentioning
confidence: 99%
“…In this 650,000-person outbreak, there were 588 COVID-19 deaths, and only 5% of these fatal COVID-19 cases were vaccinated. An elegant, matched case-control study by Shanghai CDC and Fudan University scientists, led by Dr. Huang and colleagues, showed that boosted primary-series vaccine effectiveness was 93% against severe COVID-19 and 96% against fatal COVID-19 -results that are nearly identical to those of McMenamin and colleagues in Hong Kong, furthering our confidence in the vaccines being used in China and emphasizing the importance of the booster dose (16).…”
mentioning
confidence: 78%